2015
DOI: 10.1166/jnn.2015.9876
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Sensing of Dopamine, Uric Acid and Ascorbic Acid Using tRGO-TiO<SUB>2</SUB> Nanocomposites

Abstract: This work reports a graphene-based nonenzymatic electrochemical sensing platform for the detection of dopamine (DA), uric acid (UA), and ascorbic acid (AA). Graphene oxide, synthesized by modified Hummers method, was thermally reduced in an induction furnace at 200 °C in an Ar-H2 atmosphere to obtain thermally reduced graphene oxide (tRGO). Nanocomposites of tRGO-TiO2 were obtained by a hydrothermal method, and were characterized using Fourier transform infrared (FTIR) spectroscopy, scanning electron microscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…Various TMOs have been reported to composite with rGO for the excellent trace level sensing of DA in presence of the interfering groups. Some of these selective sensors include MnO 2 /rGO by He et al, [29] rGO-Cu 2 O nanocomposite by Sivasubramanian et al, [109] Fe 3 O 4 /rGO nanocomposite by Rani et al [110] and rGO-TiO 2 nanocomposites by Rajamani et al [111] Another alternative for materials compositing with TMOs is highly conducting, tensile, and stable carbon nanotubes (CNT). Mphuthi et al doped phthalocyanine with Fe 3 O 4 and ZnO nanoparticles to couple with CNT [112] and Adekunle et al introduced iron oxide-CNT nanocomposites for the detection of DA.…”
Section: Tmos and Their Composites For The Electrochemical Sensing Of Damentioning
confidence: 99%
See 1 more Smart Citation
“…Various TMOs have been reported to composite with rGO for the excellent trace level sensing of DA in presence of the interfering groups. Some of these selective sensors include MnO 2 /rGO by He et al, [29] rGO-Cu 2 O nanocomposite by Sivasubramanian et al, [109] Fe 3 O 4 /rGO nanocomposite by Rani et al [110] and rGO-TiO 2 nanocomposites by Rajamani et al [111] Another alternative for materials compositing with TMOs is highly conducting, tensile, and stable carbon nanotubes (CNT). Mphuthi et al doped phthalocyanine with Fe 3 O 4 and ZnO nanoparticles to couple with CNT [112] and Adekunle et al introduced iron oxide-CNT nanocomposites for the detection of DA.…”
Section: Tmos and Their Composites For The Electrochemical Sensing Of Damentioning
confidence: 99%
“…[ 110 ] and rGO‐TiO 2 nanocomposites by Rajamani et al. [ 111 ] Another alternative for materials compositing with TMOs is highly conducting, tensile, and stable carbon nanotubes (CNT). Mphuthi et al.…”
Section: Tmos Assisted Non‐enzymatic Electrochemical Sensing Of Neurotransmittersmentioning
confidence: 99%
“…When compared to the metal electrodes, nanostructured metal oxide fabricated electrode materials provide some unique electrochemical characteristics and induces higher reaction rates with the exclusion of weakly adsorbed hydrogen species being present on the surface of the oxides [ 18 ]. Various types of nanostructured metal oxides, like ZnO nanowires, RGO-TiO 2 nanocomposites, RuO 2 /CNT, Fe 3 O 4 nanorods/grapheme, Fe 3 O 4 @Au nanoparticles, graphene/SnO 2 , and WO 3 nanoparticles, have been efficiently developed for the determination of DA in the biological samples [ 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. Among these electrocatalysts, distinctive properties of copper oxide (CuO) have achieved higher interest, especially in the fields of electrochemical biosensors [ 26 , 27 , 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is found that the 3D rGO showed better performance with a detection limit of 0.17 μM compared to polymer stabilized rGO. In addition various metal,− metal chalcogenide,, metal oxide based nanocomposite have been studied in this regard.…”
Section: Introductionmentioning
confidence: 99%